Development of RAPD Random Amplified Polymorphic DNA Markers for Authentification of Croton roxburghii Balak - ED, Patel (International Journal of Pharmaceutical & Biological Archive, 2013)
Development of RAPD Random Amplified Polymorphic DNA Markers for Authentification of Croton roxburghii Balak